Technique and Outcome of a Modified Tibial Plateau Levelling Osteotomy for Treatment of Concurrent Medial Patellar Luxation and Cranial Cruciate Ligament Rupture in 76 Stifles - Flesher, Kathryn; Beale, Brian S.; Hudson, Caleb C. (Veterinary and Comparative Orthopaedics and Traumatology, 2019)
Objectives The main aim of this article is to describe the technique and outcome of a modified tibial plateau levelling osteotomy (TPLO) that simultaneously levels the tibial plateau and realigns the quadriceps mechanism through medial translation of the proximal tibial segment in dogs less than 15 kg.Materials and Methods A retrospective medical records search identified dogs with concurrent cranial cruciate ligament rupture (CCLR) and medial patellar luxation (MPL). A study group (76 stifles) treated with a modified TPLO was compared with a non-tibial translation group (45 stifles) corrected with traditional surgical technique. Signalment, arthroscopic findings, adjunctive surgical procedures, osteotomy healing time and complications were recorded. Tibial plateau angle, proximal tibial segment medialization, width of the tibial osteotomy, mechanical medial proximal tibial angle and mechanical medial distal tibial angle were measured and recorded on preoperative and postoperative radiographs.Results Overall complication rate was 18.4% in the treatment group and 28.9% in the non-tibial translation group. Reluxation occurred in 6.6% of cases in the study group and in 8.8% of cases in the non-tibial translation group. There was no statistical difference in healing time between groups.Clinical Significance A modified TPLO can be used to treat patients with concurrent MPL and CCLR with good clinical outcome. Complication rates are comparable to traditional repairs for MPL. No major differences were appreciated between study and a non-tibial translation groups for variables compared.
Keywords: canine cruciate ligament rupture; dog; tibial plateau levelling osteotomy; medial patellar luxation